Analysis of iron in-use stocks in China. (September 2016) - Yue, Qiang; Wang, Heming; Gao, Chengkang; Du, Tao; Li, Mingjun; Lu, Zhongwu
Abstract: The continuous rapid increase of steel production and consumption in China since the year 2000 has led to a substantial shift in iron stocks from lithosphere to anthroposphere, making it essential to perform an in-use stock analysis of iron for China. The top-down and bottom-up methods—the most widely used approaches in analyzing in-use metal stocks—are simply introduced. Two other methods, the average use life method and the fixed assets depreciation method, are employed in this study and their results compared. The average use life method is used to analyze Chinese iron in-use stocks and the average age. Some results are obtained: iron in-use stock was 5523.9 million tons in 2013 and average age was relatively high in the period 1993–2000 (about 8.2 years) and dropped after the year 2000. The fixed asset depreciation method is applied to analyze depreciated iron in-use stock and gross domestic product (GDP) generated per unit depreciated iron in-use stock for China. The results demonstrated that the use efficiency of iron in-use stock slowly increased during the period 1993–2002, but has continually decreased since the year 2002. Scenario analysis of future iron in-use stock per capita in China is presented and the corresponding average age and GDP generated per unit depreciated iron in-use stock are calculated. Highlights: It is essential to perform an iron in-use stock (IIS) analysis for China. Average use life method (AULM) and fixed assets depreciation method (FADM) are employed. AULM is used to analyze Chinese iron in-use stocks and the average age. FADM is applied to analyze depreciated IIS and corresponding GDP generated for China. Future IIS per capita in China is forecast and the corresponding indices are calculated.